Low-frequency (0.7-7.4 mHz) geomagnetic field fluctuations at high latitude: frequency dependence of the polarization pattern - Lepidi, S.; Francia, P.; Cafarella, L. (Annals of Geophysics, 2001)
A statistical analysis of the polarization pattern of low-frequency geomagnetic field fluctuations (0.7-7.4 mHz) covering the entire 24-h interval was performed at the Antarctic station Terra Nova Bay (80.0°S geomagnetic latitude) throughout 1997 and 1998. The results show that the polarization pattern exhibits a frequency dependence, as can be expected from the frequency dependence of the latitude where the coupling between the magnetospheric compressional mode and the field line resonance takes place. The polarization analysis of single pulsation events shows that wave packets with different polarization sense, depending on frequency, can be simultaneously observed.